Extract Mushroom (Volvariella volvaceae) As a Stimulator Increased Hemoglobin Animal Test - Andi Fatmawati Muharram; Nurlia Naim; A Heri S (Universitas Hasanuddin, 2018)
This study aims to determine the ability of extracts of edible mushroom to increase hemoglobin rabbit. The method used is by using a photometer Cyanmethemoglobin C-206 Biochemyistri. Observations made with three times the measurement of hemoglobin, the measurement of the initial Hb, after induced, and after treatment. Extract of mushroom with a concentration of 2%, 4%, and 6% w/v to increase hemoglobin in test animals rabbits respectively 11.8%, 35.54%, and 79.32%. Extract with a concentration of 6% w/v had no significantly different effect with the provision of suspension ferosi sulfate 0.117% w/v, namely 86.9%. Analysis results obtained by the method ANAVA Fhitung > Ftabel at α = 0.05 and α = 0.01 with the value of each 275.52 > 275.52 3.48 and > 5.99, which means the results obtained that there are significant significant differences in the effects of each treatment.